Influence of sowing time on the yield of fodder grasses - Mussina, M.; Sarsengaliyev, R.; Ayupov, Y.; Nurgaliyeva, G.; Amangeldikyzy, Z. (IOP Conference Series: Earth and Environmental Science: International Scientific and Practical Conference on Improving Energy Efficiency, Environmental Safety and Sustainable Development in Agriculture: EESTE 2021, 2021)
Cultivated alfalfa is a species native to the Middle East and the most abundant food species in the world. In much of the dry steppe zone of Western Kazakhstan, it is the most important legume fodder crop grown for hay, dehydrated feed, pellets and silage. Alfalfa is also particularly important for restoring soil fertility: without the cost of nitrogen, residues increase soil organic matter, the root system mobilizes nutrients deep in the soil profile and soil, improves structure, water permeability and water retention. In addition, alfalfa requires only a small amount of herbicides and pesticides and no N-fertilization. This is consistent with EU policy and public concern about the environmental impact of agricultural activities. Alfalfa hay fields have also been shown to be highly beneficial for enriching biodiversity. Its high protein content meets the demands of the feed market, especially after the problems caused by the use of concentrates of animal origin, currently banned in the EU. The process of growth and development of plants is directly related to the biological characteristics of their development. All available phenological observations of the growth and development of crops provide an assessment of the conditions that ensure their productivity. The peculiarities of the growth and development of plants, caused by the deficiencies of at least one of the conditions of their vital activity, lead to a delay, and sometimes to a cessation of their growth. In this regard, the intensity of growth, and with this the level of their fodder significance, can serve as indicators of their provision with the necessary living condition.Культивируемая люцерна - это вид, произрастающий на Ближнем Востоке, и самый распространенный пищевой вид в мире. На большей части сухостепной зоны Западного Казахстана это важнейшая бобовая кормовая культура, выращиваемая на сено, обезвоженные корма, гранулы и силос. Люцерна также особенно важна для восстановления плодородия почвы: без затрат азота растительные остатки увеличивают органическое вещество почвы, корневая система мобилизует питательные вещества глубоко в почвенный профиль и почву, улучшает структуру, водопроницаемость и водоудержание. Кроме того, люцерне требуется лишь небольшое количество гербицидов и пестицидов и никаких азотных удобрений. Это соответствует политике ЕС и озабоченности общественности воздействием сельскохозяйственной деятельности на окружающую среду. Также было показано, что сенокосы с люцерной очень полезны для обогащения биоразнообразия. Его высокое содержание белка отвечает требованиям рынка кормов, особенно после проблем, вызванных использованием концентратов животного происхождения, которые в настоящее время запрещены в ЕС. Процесс роста и развития растений напрямую связан с биологическими особенностями их развития. Все имеющиеся фенологические наблюдения за ростом и развитием сельскохозяйственных культур дают оценку условий, обеспечивающих их продуктивность. Особенности роста и развития растений, вызванные дефицитом хотя бы одного из условий их жизнедеятельности, приводят к задержке, а иногда и к прекращению их роста. В связи с этим интенсивность роста, а вместе с тем и уровень их кормовой значимости, могут служить показателями обеспеченности их необходимыми жизненными условиями.
Keywords: импакт-фактор 2022; скопус; scopus; конференции; дальнее зарубежье; люцерна; кормовые культуры; зко; бобовая кормовая культура; сено